High‐Temperature Shock Enabled Nanomanufacturing for Energy‐Related Applications. Issue 33 (21st July 2020) - Dou, Shuming; Xu, Jie; Cui, Xiaoya; Liu, Weidi; Zhang, Zhicheng; Deng, Yida; Hu, Wenbin; Chen, Yanan
Abstract: Functional nanomaterials are playing a crucial role in the emerging field of energy‐related devices. Recently, as a novel synthesis method, high‐temperature shock (HTS), which is rapid, low cost, eco‐friendly, universal, scalable, and controllable, has provided a promising option for the rational design and synthesis of various high‐quality nanomaterials. In this report, the HTS technique, including the equipment setup and operating principle, is systematically introduced, and recent progress in the synthesis of nanomaterials for energy storage and conversion applications using this HTS method is summarized. The growth mechanisms of nanoparticles and carbonaceous nanomaterials are thoroughly discussed, followed by the summary of the characteristic advantages of the HTS strategy. A series of nanomaterials prepared by the HTS method, including carbon‐based films, metal nanoparticles and compound nanoparticles, show high performance in the diverse applications of storage energy batteries, highly active catalysts, and smart energy devices. Finally, the future perspectives and directions of HTS in nanomanufacturing for broader applications are presented. Abstract : This progress report systematically introduces the high‐temperature shock (HTS) technique, a nanomanufacturing technique that enables rapid reaction, high‐efficiency and low‐cost. The recent progress in the synthesis of nanomaterial employing HTS method for energy storage and conversion applications is summarized. Finally, the future perspectives and challenges of HTS are outlined.